Education in OECD countries 1986-87 : a compendium of statistical information - (:unkn) unknown (My University, 1989)
"This compendium of statistical information, the third in the series and the first to appear as a puplication, is based on the country replies to the joint UNESCO/OECD/SOEC (Statistical Office of the European Communities) questionnaires. Like its predecessors, this compendium is divided into two parts. Part A gives a general overview of the situation as regards education in 1986-87 and presents, in the form of charts accompanied by brief summaries, a number of the main indicators for education. Part B deals with six major topics, with a chapter devoted to each: 1. pupils; 2. teachers; 3. students; 4. enrolment rates per year of age (except for the years that, for most countries, correspond to compulsory education); 5. qualifications; 6. expenditure. The right-hand pages contain both absolute figures and calculations as well as charts showing, for the most part, annual changes between 1985-86 and 1986- 87. On the left-hand pages, there is a brief commentary on the information presented and attention is drawn to any differences that may exist between the standard international definitions and those adopted by certain countries on specific items. The standard definitions are presented at the end of each chapter, along with indication of other data included in the replies to the questionnaire but not incorporated in this compendium. The compendium's Annex includes a table devoted to the age at which compulsory education begins and finishes in each OECD country, its duration, and the months in which the school year starts and finishes. The main part of the Annex, however, is the presentation of a separate diagram for each Member country, summarising each education system using the terminology of the country in question. To facilitate inter-country comparisons, the sections, and terms used to show the national system and the corresponding level or type of education following the standard definitions are coloured identically." (author's abstract) Im ersten Teil des Kompendiums zur Bildungsstatistik in den OECD- Mitgliedstaaten wird ein Überblick zur Situation des Bildungswesens 1986-87 gegeben. Der zweite Teil enthält Zahlen und Erklärungen zur Entwicklung in den einzelnen Ländern für sechs Hauptthemen: Schüler; Lehrer; Studenten; Schüler-/ Studentenzahlen nach Altersgruppen; Qualifikationen; Bildungsausgaben. Der Anhang bringt für jedes OECD-Mitgliedsland ein Diagramm zum Aufbau des jeweiligen Bildungssystems. (IAB)
Bildung in der OECD-Ländern. Ein Kompendium statistischer Informationen
Keywords: S 1 Stufen der Berufsbildung; G 2.3.5 Wirtschaftsstrukturwandel; S 4 Kosten & Finanzierung; T 3.5 Statistik; G 1.1.4 Statistiken zu speziellen Problemlagen & Bereichen; P 3.2.3 Lehrer; S 1.1 Allgemeinbildende Schule; P 2.1.5 Fachhochschul- und Hochschulreife; G 1.3.1 Bildungsangebot & -nachfrage; Bildungsstatistik; Internationaler Vergleich; Bildungssystem; Struktur; Bildungsausgaben; Statistik; Schülerzahl; Lehrer; Schulwesen; Allgemeinbildendes Schulwesen; Berufsbildendes Schulwesen; Hochschulzugang; Hochschule; Bildungsabschluss; Geschlechtsspezifische Faktoren; Quantitative Angaben; OECD